The Mill on the Floss : la pluralité générique selon George Eliot - Jean-Charles Perquin (Cahiers Victoriens et Edouardiens)
George Eliot’s The Mill on the Floss is obviously the result of generic interferences, the diegesis borrowing a lot from the traditional family saga, but also from the complex structure of classical tragedy, Eliot’s understanding of the direct social consequences of Darwin’s theories, and the oblique presence of the supernatural with the final overflowing of the Floss.The Mill on the Floss is thus a novel whose structure is wholly based on the blending of several types and subgenres. The novel itself depends on the combination of several discourses, which enrich each other and obliquely create the conditions of their compatibility. The very end of the novel thus benefits from the melodramatic dimension and tradition it seems to imitate, whereas the novel itself cannot be termed a melodrama. In The Mill on the Floss, each subgenre directly redefines George Eliot’s novel and creates the possibility of the blending of different genres and types.